TRAFFIC NOISE EXPERIENCED ON BUSES, TRAMS AND CARS IN THE URBAN AGGLOMERATION OF THE CITY OF KATOWICE - Agata MICHTA; Tomasz HANISZEWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
Transport noise is one of the biggest problems faced by urban agglomerations. Therefore, more and more activities are being undertaken related to its reduction. The article attempts to investigate the noise level on public transport vehicles, buses, trams and passenger cars, from the passenger’s perspective. The assessment is based on the results of field tests. The study considered wheeled and rail vehicles, including a new generation of buses and tramways, as well as a car subjected to many years of operation. The research was carried out in the city of Katowice. The conducted experiment showed comparable high values for recorded volume levels on trams and buses, as well as a relatively low noise level in the passenger car.